Short-Segment Fixation of Thoracolumbar Burst Fracture: Plate vs. Rod Systems The Results Obtained by Adding Pedicular Screws at the Level of Fracture - Meelab, MD, P (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To evaluate the effect of short-segment pedicle screw fixation of thoracolumbar unstable burst fractures by adding pedicle screws at the level of fracture; and to compare the pedicle plate and pedicle rod systems. Material and Method: A retrospective study to evaluate 20 patients with unstable thoracolumbar burst fractures, admitted to Saraburi Hospital from 2006 to 2009. All underwent short-segment pedicle screw fixation with added pedicle screws at the level of fracture. A review of the medical records, including radiographs was completed. The pedicle screw fixation was classified into two types: a plate or a rod system. Evaluation was based on the correction of kyphotic deformity from the time of surgery to at least the end of a six month follow-up period. Results: Twenty patients underwent short-segment pedicle screw fixations (8 plate, and 12 rod systems) with added screws at the level of injury. Surgical correction of kyphotic deformity from 18.4 degrees to 5.10 degrees was obtained. This was of statistical significance, and the correction maintained until fracture union, with only slightly progressive kyphotic deformity. No significant difference was encountered in the comparison of the efficacy of the pedicle plate and the pedicle rod systems. Conclusion: Short-segment pedicle screw fixation remains popular in the treatment of thoracolumbar burst fractures. Adding pedicle screws at the level of injury results in increased stability of the system, and decreases complications. Both pedicle plate and rod systems yield similar clinical outcomes.